2022
DOI: 10.3389/fncir.2022.799581
|View full text |Cite
|
Sign up to set email alerts
|

Neural Substrates and Models of Omission Responses and Predictive Processes

Abstract: Predictive coding theories argue that deviance detection phenomena, such as mismatch responses and omission responses, are generated by predictive processes with possibly overlapping neural substrates. Molecular imaging and electrophysiology studies of mismatch responses and corollary discharge in the rodent model allowed the development of mechanistic and computational models of these phenomena. These models enable translation between human and non-human animal research and help to uncover fundamental feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 123 publications
3
15
0
Order By: Relevance
“…Stimulus omissions are another form of contextual novelty in which expectation is violated, i . e ., a predicted input does not occur (Braga and Schönwiesner, 2022). In sessions with familiar stimuli, we found that Vip activity showed ramping behavior during the inter-stimulus interval and continued to ramp up during unexpected omissions.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Stimulus omissions are another form of contextual novelty in which expectation is violated, i . e ., a predicted input does not occur (Braga and Schönwiesner, 2022). In sessions with familiar stimuli, we found that Vip activity showed ramping behavior during the inter-stimulus interval and continued to ramp up during unexpected omissions.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, ramping activity in Vip cells could represent more general information about task timing (Rabinovich et al, 2022), temporal expectation (Nobre et al, 2007), prediction error (Orlova et al, 2021;Wacongne et al, 2011), salience (Itti and Koch, 2001), stimulus contrast (Millman et al, 2020) or a combination of these (Braga and Schönwiesner, 2022).…”
Section: Vip Omission Signals Are Reduced By Noveltymentioning
confidence: 99%
See 3 more Smart Citations